Beyond human limits: the ethical, social, and regulatory implications of human enhancement - Chiara Gerardi; Christodoulos Xinaris (Frontiers in Medicine, 2025)
Human enhancement involves interventions that enhance physical or cognitive performance or overall wellbeing beyond typical human limits. The consequence of human enhancement has the potential to radically reshape society and the very existence of our species, requiring careful consideration of its ethical and regulatory boundaries. In this paper, we explore current applications of human enhancement, including motor neuro -prostheses, transcranial magnetic stimulation, and gene therapy. We analysed key unresolved challenges and potential solutions, focusing on regulatory and policy frameworks, ethical considerations in clinical research, transparency through registries, traceability of interventions, and the role of informed decision-making and consent. Finally, we critically examine the evolving definition of health and the need to delineate clear boundaries between prevention and enhancement. By addressing these issues, this paper aims to contribute to the ongoing dialog on the responsible development and implementation of human enhancement technologies.